Assessing the effectiveness of workplace accommodations in facilitating return to work after traumatic brain injury: a systematic review protocol. Issue 5 (19th May 2021) - Shafi, Reema; Colantonio, Angela
Abstract : Introduction: Returning to work and sustaining employment can be a significant challenge for traumatic brain injury (TBI) survivors. Within the literature, there is recurring support for the role of workplace accommodations in effective and early return-to-work (RTW). To date, however, there has been a lack of systematic reviews exploring the specific role of workplace accommodations within the context of RTW after TBI. The primary objective of this protocol is to outline the methodological approach that will be undertaken to systematically review the literature and to assess the effectiveness of workplace accommodations in facilitating RTW. Methods and analysis: A total of nine databases will be searched systematically using the concepts 'Brain injury, ' 'RTW' and 'Job Accommodations.' Study selection will be performed independently by three reviewers, based on predetermined eligibility criteria through two rounds of screening using, first, the title and abstract, followed by a full-text search. Extracted information will include the study's purpose, design, and setting; the data source and type; the severity of TBI and the diagnostic criterion used; a comprehensive description of the intervention provided; the RTW outcome variables and the statistical methods used, etc. The data will be tabulated and narratively synthesised. Systematic review registration: This protocol has been registered with International Prospective Register of Systematic Reviews. Ethics and dissemination: As this review intends to use pre-existing published studies hence research ethics board approvals will not be required. Nevertheless, this review will follow the ethical and governance standards in the data management and presentation of results. The findings from this review will potentially be published in a peer-reviewed scientific journal (electronically and in print). The results of this review will be presented at both national/international conferences and shared with stakeholders influencing RTW practices. PROSPERO registration number: CRD42016043517.